The cultural value of art in the age of barbarism: Michel Henry’s aesthetic phenomenology - Palomar Torralbo, Agustín (Estudios de Filosofía, 2018)
In this work, barbarism is assumed as the key political question and it is examined through the view of Michel Henry ́s aesthetic phenomenology. Firstly, this paper reflects upon the new concept of barbarism, which is described by Michel Henry as the prevalence of the concept of objectivity created by science and technology over life. Secondly, it presents the concept of culture as an original manifestation of life; a concept that opposes, therefore, to the theoretical knowledge of science. Finally, the paper highlights the way art restores the sense of culture which has been displaced by barbarism in our times.